problem 1
in the equation x - y = 1, solve for x in terms of y.
replace x in either of the other two equations and you will be able to solve for x. Now, you can go back to any of the three equations and replace x with the value you found and solve for y.
Check that your solution for x and y satisfy all three equations.
I cannot solve these last three systems. Could you show me the work for them so i understand how to do them.
1)
x-y=1
2x+y=5
3x-4y=2
2)
5x+8y+6z=14
2x+5y+z=12
-3x+6y-12z=20
3)
x^2+2xy-2y^2=-11
x^2+xy-2y^2=-9
2 answers
1)
x-y=1
x = 1 + y
2x+y=5
2(1 + y) + y = 5
2 + 2y + y = 5
3y = 3
y = 1
3x-4y=2
3x - 4 = 2
3x = 6
x = 2
x-y=1
x = 1 + y
2x+y=5
2(1 + y) + y = 5
2 + 2y + y = 5
3y = 3
y = 1
3x-4y=2
3x - 4 = 2
3x = 6
x = 2